DAMPAK PERTUMBUHAN PENDUDUK TERHADAP LINGKUNGAN DAN BUDAYA SUBAK : STUDI KASUS DI KABUPATEN TABANAN PROVINSI BALI - Wardi, I Nyoman; Laksmiwati, I.A Alit; Gunadi, I Gusti Alit; As-syakur, Abd Rahman (Bumi Lestari, 2016)
The research aims to reveal the trens population growth over the 10 years (2002-2012) in Tabanan Regency, as well as their impact on the land conversion of subak as well as other changes in environmental and cultural aspects of subak. Research conducted through the stages of data collection and data analysis. The technique of data collection was done by the library research, observation, and structured interviews with questionnaires and indepth interviews (depth interview).The data collected was analyzed by descriptivequalitative and quantitative analysis with the help of cross-tables and analysis of satellite imagery. Results of the study showed, the number of inhabitants of Tabanan Regency in 2012 reached 441.900 people, consisting of 220. 002-sex guy men and 221.898 women. The livelihoods of inhabitants, mostly working in the agricultural sector (110.449 people) and plantations (45,326 people). Based on analysis conducted, it was revealed that within the last 10 years (2002-2012) population growth reached 26,10% or = 2.61% per year. The highest growth occurred in the district of Kediri 5,76%, then followed by district of  Baturiti 5.13%, Marga 4.05%, and district of  Tabanan, 3,69%. The lowest population growth occurred in district Penebel 0.34%, then followed by the district of Kerambitan 0,56% and district of East Selemadeg 0.82%. The population growth seems to be more of a factor caused by migration (people coming) 62,24% (1294 inhabitants) (from the difference in population that comes 3293 with people out 1999 inhabitants), if compared with population growth naturally only achieve 37,76% (785 inhabitants). The population growth indirectly affects the occurrence of changes in the environment and culture of subak. In the past 10 years occurred the shrinking land subak (fields) 672,89 ha, or 2.95% of the total area of paddy fields in 2002 (22.842 fare ha). Other environmental effects, i.e. reduced water supply and the breakdown in some irrigation farmers, pollution and the impact of irrigation channel blockage by garbage plastic and aesthetic degradation of the environment. Socio-cultural impact of subak, which tendency to the occurrence of social conflict, disruption in the silent  ritual of rice fields (penyepian carik) and the abandonment of cultural heritage (pura subak) due to the occurrence of function fields into housing and tourism facilities. The protection needs to be done to the environment and subak culture through the population growth control with government policy, the formulation of customary law of subak (awigawig), and improve the welfare of farmers through the development of ecotourism that based on subak ecosystem.
Keywords: population, impact, subak, ecotourism.